RESEARCH OF A MATHEMATICAL MODEL IN AFT PRODUCTION - Nastinov Sadriddin Tojiddin o‘g‘li; Abdukodirov Elbek Abduvali ugli (Sciental Journals Publishing, 2025)
In this work, a mathematical model of the process of antiplaque (AFT) formation in the oral cavity was developed and analyzed. AFT is a biofilm formed by microorganisms, which leads to the development of caries, gingivitis and other periodontal diseases. In the study, the main stages of AFT formation: bacterial colonization, biofilm growth and salivary flow clearance processes were mathematically modeled. A dynamic model was built based on ordinary differential equations (ODE) and simulated using MATLAB/Python. The results show a functional relationship between the level of AFT and hygiene factors.
Keywords: AFT, biofilm, mathematical model, oral hygiene, differential equation, simulation